Primary reconstruction of depressed skull fracture - Khan, Arshad; Shrivastava, Nishant; Pal, S. S. (International Surgery Journal, 2018)
Background: Depressed fracture poses a specific challenge to neurosurgeon. Aim of our study is to analyze benefits of primary reconstruction of depressed skull fracture and to compare various methods of fracture reconstruction with that of titanium miniplates The concept of primary reconstruction was to close the defect and preserve the anatomical barrier, to avoid later crainoplasty and to prevent further complications like CSF leak, pneumocephalus, brain fungus and meningitis etc. The second reason for rigid fixation was to achieve good cosmetic results. Methods: This is observational study carried out in Department of General Surgery, Hamidia hospital Bhopal on 36 patients over period of 18 months from January, 2016 to July, 2017. Results: : Depressed skull fracture is more prevalent in second and third decade of life with male to female ratio of 5:1 . Most of the patients (72%) presented with open fracture skull and majority of them (89%) presented with underlying brain injury. Out of total 36 patients of depressed fracture skull, 18 patients (50%) underwent fixation with titanium miniplate and rest underwent fixation with nylon suture, Poly-L-Lactide and primary elevation of depressed skull fracture. The correction of deformity was more than 90% compared to contralateral side and better cosmetic results were obtained on patients treated with titanium mini-plates. Post operative infection rate was nil in patient treated with titanium mini-plates compared to 8.2% of total infection rates in patients treated with other methods. Conclusions: The concept of primary reconstruction of depressed skull fracture to achieve better cosmetic results and minimum post operative complications. Cosmetic results that were obtained with titanium mini-plates were excellent with nil post operative infection rates and complete neurological recovery. Hence titanium mini-plates are cost effective and better than any other methods.